Correlation of the peripheral perception with the maturation and the effect of the peripheral perception on the tactical behaviour of soccer players - Gonçalves, E.; Noce, F.; Barbosa, M. A. M.; Figueiredo, A. J.; Hackfort, D.; Teoldo, I. (International Journal of Sport and Exercise Psychology, 2020)
The purpose of this study was to (1) verify the correlation between maturation and peripheral perception and (2) to analyse the effect of peripheral perception on the efficiency of tactical behaviour in young soccer players. Fifty-four (U-11, U-13 and U-15) young male soccer players participated in the study. The maturation was evaluated by the Khamis-Roche method, the peripheral perception by a computer-based test in the Mental Test and Training System, and the efficiency of the tactical behaviour by the System of Tactical Assessment in Soccer. Descriptive analysis, Kolmogorov-Smirnov, Spearman bivariate correlation, and multivariate analysis of variance tests were performed. The significance level adopted was p < .05. Correlations have been observed between the percentage of predicted adult height and the performance in peripheral perception. It was also detected that the peripheral perception has an effect on the efficiency of the tactical behaviour in young players. It has been concluded that the maturation of an individual has an association with the peripheral perception, and that it can make players more efficient to perceive the environment and in the execution of fundamental tactical principles of the soccer game.